A Hybrid Group Decision-Making Approach for Prioritizing Regional Development Programmes in South Sulawesi Province, Indonesia - Kurnia, Yahya (2024)
This research developed a Group Decision Support System (GDSS) to support decision makers in ranking the regional development programmes for South Sulawesi Province in Indonesia to overcome the development gap towards national development stability. Determining regional development programs in Indonesia necessitates the involvement of multiple decision-makers (DMs), including the government, investors, universities, community organizations, and non governmental organizations, to facilitate group decision making. There are always procedures involved when using a decision-making system, especially when deciding which regional development program to be prioritised among several possible alternatives. Implementation of the regional development programmes in Indonesia has not fully taken into account the scale of priorities and elements of justice. In carrying out regional development programmes, it was found that there are development programmes that were prioritized, actually not according to regional development criteria. This has resulted in regional development programmes in Indonesia not in accordance with the targets to be achieved. Hence, it would cause development gaps, which impacted on national development stability. Determining regional development program priorities often does not pay attention to whether there is a link with the target indicators set in The Medium-Term Regional Development Plan (RPJMD). This results in budget inefficiencies, social injustice and unsustainable programs. Therefore, the objectives of this research are :- to identify a new ranking model for prioritising regional development programs in South Sulawesi Region, to develop a new decision-making technique for Decision Makers in determining the priority scale according to the criteria set out in the regional development program in South Sulawesi Province, to develop a new group decision making technique for a group Decision Maker in determining priorities which are aligned with the specified criteria in the regional development program in South Sulawesi Province and to validate the developed Group Decision Support System in identifying the priority in regional development programs. This research developed Group Decision Support System based on decision ranking models for regional development program namely AHP, ELECTRE, ARAS, AHP+ ARAS, AHP+ELECTRE, ELECTRE+ARAS, and AHP+ELECTRE+ ARAS. Based on the accuracy test, it was found that GDSS based on hybrid AHP + ELECTRE + ARAS method resulted in the highest accuracy which is 86.67%. The prioritised regional development programs obtained from the developed hybrid AHP + ELECTRE + ARAS Group Decisions Support System were also validated by experts review which show strong correlation. The prioritised regional development programs determined from the developed Group Decisions Support System will be used as recommendations for regional development programs implementation.